(untitled) (Journal of Interdisciplinary Insights, 2024)
This qualitative study explores teaching strategies for university dance education in the internet era, focusing on the challenges and opportunities presented by online instruction. Conducted at Hebei University, the research involved semi-structured interviews with 30 participants, including dance instructors and students. Thematic analysis of the interview data revealed key themes related to adaptation to online platforms, technological integration, enhanced accessibility and flexibility, challenges of engagement and interaction, pedagogical adjustments, and the emotional and psychological impact of online dance education. Case studies illustrate these themes, highlighting strategies employed by instructors and students to navigate the transition to online learning. The findings underscore the importance of innovative pedagogical approaches, technological infrastructure, and student-centered learning strategies in online dance education. Implications for teaching strategies and recommendations for practice are discussed, emphasizing the need for ongoing professional development, community building, and a commitment to excellence in online dance education.